2015
DOI: 10.1287/mnsc.2014.1927
|View full text |Cite
|
Sign up to set email alerts
|

Are Good-Looking People More Employable?

Abstract: Job applicants in Europe and in Israel increasingly imbed a headshot of themselves in the top corner of their CVs. We sent 5312 CVs in pairs to 2656 advertised job openings. In each pair, one CV was without a picture while the second, otherwise almost identical CV contained a picture of either an attractive male/female or a plain-looking male/female. Employer callbacks to attractive men are significantly higher than to men with no picture and to plain-looking men, nearly doubling the latter group. Strikingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
111
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 28 publications
(9 reference statements)
10
111
4
Order By: Relevance
“…find a gender-specific effect of attractiveness, namely a beauty premium for males and a beauty penalty for females, while LópezBóo et al (2013) find a beauty premium for both genders. The beauty penalty observed byRuffle and Shtudiner (2014) is most consistent with jealousy, a type of taste-based discrimination that may not arise in our setting due to limited interactions between workers and employers. It is unclear whether the beauty premium found by LópezBóo et al (2013) is based on tastes or is statistical.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…find a gender-specific effect of attractiveness, namely a beauty premium for males and a beauty penalty for females, while LópezBóo et al (2013) find a beauty premium for both genders. The beauty penalty observed byRuffle and Shtudiner (2014) is most consistent with jealousy, a type of taste-based discrimination that may not arise in our setting due to limited interactions between workers and employers. It is unclear whether the beauty premium found by LópezBóo et al (2013) is based on tastes or is statistical.…”
supporting
confidence: 60%
“…SeeWilson and Eckel (2006) for beauty and learning in a trust game andAndreoni and Petrie (2008) andCastillo et al (2012a) for beauty and learning in a public goods game, among others.3 Dermer and Thiel (1975) document that certain socially undesirable characteristics, such as egotism and materialism, are ascribed to relatively attractive females Ruffle and Shtudiner (2014). find a beauty penalty for attractive female job applicants Wilson and Eckel (2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IJM 36,1 A previous resume audit study conducted by Ruffle and Shtudiner (2014) for the Israeli labor market finds that employers call back men with attractive photos attached to their resumes at twice the rate of those with no photo or those with a plain-looking photo attached. Their study also reports that women with attractive photos attached to their resumes are penalized, that is, they have a significantly lower callback rates than women with no photos.…”
mentioning
confidence: 99%
“…Ruffle and Shtudiner (2015), however, found that only attractive males benefited. They found that attractive females were prejudiced, postulating that such prejudice was envy based.…”
Section: Bias In Selectionmentioning
confidence: 94%